Effect of Dietary Supplementation of Aloe Vera (Aloe barbadensis) on Growth Performance and Nutrient Utilization Efficiency in Broiler Chicken - Yadav, Dipin Chander; Bidhan, Devender Singh; Gulati, Harish Kumar; Sihag, Sajjan; Sharma, Vishal (Indian Journal of Animal Nutrition, 2017)
An experiment was conducted to study the effect of three forms of aloe vera viz. powder, gel and juice on growth, feed intake, feed conversion ratio (FCR), energy efficiency (EE), protein efficiency (PE) and mortality in broiler chickens. A total of 240 day-old chicks were randomly allotted to four treatment groups withfour replicates having fifteen broiler chicks in each replication. The chicks were fed with standard basal diets in three different growth phases i.e. pre-starter (0-7d), starter (8-21d) and finisher (22-42d). The control group T1 was fed a basal diet (BIS, 2007). The birds in group T2 were fed control diet as in T1 + aloe vera powder @ 0.5%; in group T3: control diet as in T1 + aloe vera gel in feed @ 2% and in group T4: control diet as in T1 + fresh aloe vera juice in drinking water @ 2%. The body weight gains were not affected due to supplementation of different forms of aloe vera. However, supplementation of aloe vera improved (P